2018
DOI: 10.3390/antiox7040054
|View full text |Cite
|
Sign up to set email alerts
|

Iron and the Breastfed Infant

Abstract: The first 6 months of life is a crucial time in meeting iron needs. The purpose of this review is to examine iron in mother’s milk and whether or not it meets the physiological needs of the growing infant. Key issues include iron content and iron transport from the mammary gland as well as when and what foods should be added to the solely breastfed infant. We examine these topics in light of new molecular biology findings in the mammary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 66 publications
(103 reference statements)
1
29
0
1
Order By: Relevance
“…Recent studies have indicated that iron content in breast milk is low [12][13][14], and prolonged use of breast milk as the main food in infants might increase the risk of ID and IDA [15]. In Taiwan, the Ministry of Health and Welfare promotes the benefits of breastfeeding for a long period.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that iron content in breast milk is low [12][13][14], and prolonged use of breast milk as the main food in infants might increase the risk of ID and IDA [15]. In Taiwan, the Ministry of Health and Welfare promotes the benefits of breastfeeding for a long period.…”
Section: Introductionmentioning
confidence: 99%
“…The largest effects were observed among mothers in the lower quantiles, suggesting that interventions to promote breastfeeding among lactating mothers may have more impact on Hb concentration of mothers at the lower end of the Hb distribution. These findings may appear puzzling because it is generally believed that lactating mothers tend to lose some iron to their infants, which may have a bearing on their Hb concentration 38,39 . Nevertheless, other evidence suggests that the iron contained in breast milk to children is not significant enough to deplete the iron level of the mother unless the mother is already anaemic 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the low concentration of iron in mature breast milk ( 51 , 52 ) and low prevalence of breast-feeding in this population, we did not include iron intake from breast milk in our modeling. We did a sensitivity analysis by including estimated iron from breast milk in total iron intakes (assuming concentrations of 0.2 mg iron/L, 0.549 L milk/d, and 50% absorption of breast milk iron); this addition had no substantial effect on the prevalence of inadequate intake or effective coverage.…”
Section: Methodsmentioning
confidence: 99%